Are the current Australian sun exposure guidelines effective in maintaining adequate levels of 25-hydroxyvitamin D?. Issue 155 (January 2016) - Kimlin, Michael; Sun, Jiandong; Sinclair, Craig; Heward, Sue; Hill, Jane; Dunstone, Kimberley; Brodie, Alison
Highlights: Winter sun exposure guidelines for 25(OH)D adequacy are hard to follow. Following sun exposure guidelines in winter does not ensure adequate 25(OH)D status. Summer sun exposure guidelines are easy to follow. Abstract: An adequate vitamin D status, as measured by serum 25-hydroxyvitamin D (25(OH)D) concentration, is important in humans for maintenance of healthy bones and muscle function. Serum 25(OH)D concentration was assessed in participants from Melbourne, Australia (37.81S, 144.96E), who were provided with the current Australian guidelines on sun exposure for 25(OH)D adequacy (25(OH)D ≥50 nmol/L). Participants were interviewed in February (summer, n  = 104) and August (winter, n  = 99) of 2013. Serum 25(OH)D concentration was examined as a function of measures of sun exposure and sun protection habits with control of key characteristics such as dietary intake of vitamin D, body mass index (BMI) and skin colour, that may modify this relationship. The mean 25(OH)D concentration in participants who complied with the current sun exposure guidelines was 67.3 nmol/L in summer and 41.9 nmol/L in winter. At the end of the study, 69.3% of participants who complied with the summer sun exposure guidelines were 25(OH)D adequate, while only 27.6% of participants who complied with the winter sun exposure guidelines were 25(OH)D adequate at the end of the study. The results suggest that the current Australian guidelines for sun exposure for 25(OH)D adequacy are effective for most in summer and ineffective for most in winter. This article is part of a Special Issue entitled '17th Vitamin D Workshop'.